Global evolution and paleogeographic distribution of mid-Cretaceous orbitolinids. Issue 1 (2nd August 2019) - BouDagher-Fadel, Marcelle; Price, Geoffrey David
Abstract : Members of the Larger Benthic Foraminiferal (LBF) family Orbitolinidae occurred from the Cretaceous to the Paleogene, however, they were most diverse during the mid-Cretaceous, and dominated the agglutinated LBF assemblages described from limestones of that period. Various orbitolinid species have been used to zone and date lithologies formed in the shallow, warm waters of the Aptian to the early Cenomanian, and many, sometimes inaccurate, generic and sub-generic nomenclatures have been proposed to differentiate the often-subtle morphological changes that orbitolinids exhibit over time. Also, until now, it has not been possible to develop an effective global overview of their evolution and environmental development because descriptions of specimens from Asia have been relatively rare. Following our recent study of over 1800 orbitolinid-rich thin sections of material from 13 outcrops of Langshan limestone, from the Southern Tibetan Plateau, and from the Barito Basin, South Kalimantan, Indonesia, it has been possible to compare the stratigraphic ranges of these orbitolinids with previously described Tethyan and American forms, based on the use of a planktonic zonal (PZ) scheme, itself tied to the most recent chronostratigraphic scale. This has allowed the reconstruction of the phylogenetic and paleogeographic evolution of the orbitolinids from their Valanginian origin in the Tethys. Although the Tethys remained the paleogeographic centre for the orbitolinids, it is inferred here for the first time that a bi-directional paleogeographic migration of some orbitolinid genera occurred from the Tethys to the Americas and also to the Western Pacific region. Our observations and dating suggest that global marine regressions in the Aptian were coincident with, and may well have facilitated, these orbitolinid transoceanic migrations. Migration stopped however after rising sea level in the early Albian appears to have again isolated these provinces from each other. Tectonic forces associated with the subduction of the Farallon Plate and further sea level raises led to the opening of the Western Interior Seaway in North America, which correlates with, and may have been the cause of, the middle Albian (top of PZ Albian 2) extinction of the American orbitolinids. The extinction of the orbitolinids revealed that the Western Pacific province was split into two sub-provinces, with extinction occurring at the end of the early Albian (top of PZ Albian 1) in the Northwest Pacific sub-province, and at the end of the Albian (top of PZ Albian 4) in the subprovince that is today South East Asia (on the margins and west of the Wallace Line). The final near extinction of the orbitolinids occurred at the end of the Cenomanian in the Tethyan province, which coincides with, and may have been caused by, global anoxic oceanic events that correlate with a near-peak Mesozoic eustatic sea level high-stand that led to the overall global collapse of the paleotropical reef ecosystem at that time.